2014
DOI: 10.14260/jemds/2014/3598
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Hypertension Among Adults Aged 30 Years and Above in a Rural Dwelling of Kottayam, Kerala

Abstract: INTRODUCTION:Rising prevalence of hypertension is a major public health challenge in India especially in Kerala. This cross sectional study was done to assess the prevalence of hypertension and its determinants in a rural population of Kottayam, Kerala. MATERIALS AND METHODS: Community based cross sectional study was carried out among 400 adults aged 30 years and above in a randomly selected ward of Ettumanoor panchayath, which is the field practice area of Govt. Medical college, Kottayam. A pretested semi str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Sivaprasad et al found the prevalence of hypertension was significantly higher among the subjects with low physical activity (43.6%) than those having moderate or vigorous activity (p=0.01). 20 The current study found that people who consume fruits and vegetables >2 times/day had less chance of developing pre hypertension and hypertension compared to people who consume fruits and vegetables <2 times/day and this association was statistically significant.…”
Section: Discussionsupporting
confidence: 47%
“…Sivaprasad et al found the prevalence of hypertension was significantly higher among the subjects with low physical activity (43.6%) than those having moderate or vigorous activity (p=0.01). 20 The current study found that people who consume fruits and vegetables >2 times/day had less chance of developing pre hypertension and hypertension compared to people who consume fruits and vegetables <2 times/day and this association was statistically significant.…”
Section: Discussionsupporting
confidence: 47%